2009
DOI: 10.1128/jvi.00668-09
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Endogenous Retroviruses in Crocodilians

Abstract: Knowledge of endogenous retroviruses (ERVs) in crocodilians (Crocodylia) is limited, and their distribution among extant species is unclear. Here we analyzed the phylogenetic relationships of these retroelements in 20 species of crocodilians by studying the pro-pol gene. The results showed that crocodilian ERVs (CERVs) cluster into two major clades (CERV 1 and CERV 2). CERV 1 clustered as a sister group of the genus Gammaretrovirus, while CERV 2 clustered distantly with respect to all known ERVs. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…Unsurprisingly, ERV1 and ERV4 were the predominant lineages in the genomes, with 15 and 22 groups respectively. This is in agreement with previous studies that have identified a large number of ERV1 and ERV4 insertions across crocodilian species [2,4]. The crocodilian ERVs displayed very weak associations with ERVs from other taxa and exogenous retroviral genera, suggesting that ancient ERV insertions represent intermediates or novel lineages between the currently recognised taxa.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Unsurprisingly, ERV1 and ERV4 were the predominant lineages in the genomes, with 15 and 22 groups respectively. This is in agreement with previous studies that have identified a large number of ERV1 and ERV4 insertions across crocodilian species [2,4]. The crocodilian ERVs displayed very weak associations with ERVs from other taxa and exogenous retroviral genera, suggesting that ancient ERV insertions represent intermediates or novel lineages between the currently recognised taxa.…”
Section: Discussionsupporting
confidence: 92%
“…While these criteria may bias analyses to insertions that are better preserved or more recently integrated, it also reduces the amount of sequence divergence and evolutionary 'noise' that may be introduced by the inclusion of highly degraded sequences. BLASTX [62] was used to classify the predicted pol sequences into the major ERV classes based on similarity to pro-pol and pol fragments recovered from previous studies [1][2][3][4][5]; Chong et al, unpublished data]. Sequences that showed no similarity to known crocodilian ERV fragments where then compared to other published sequences in GenBank and Repbase using the NCBI BLAST suite [63] and Censor [64].…”
Section: Definition Of Erv Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. Chong Á S. R. Kjeldsen Á J. Gongora (&) Faculty of Veterinary Science, The University of Sydney, Sydney, Australia e-mail: jaime.gongora@sydney.edu.au [8]. PCR amplification, bacterial cloning, and sequencing were carried out as previously described [2,3] using universal primers targeting the region between highly conserved, functional, retroviral motifs from the pro-pol region [9].…”
Section: Methodsmentioning
confidence: 99%
“…Crocodilians (Crocodylia) have been shown to harbour a particularly diverse range of ERVs, including the newly described ERV4 [2][3][4][5][6]. Previously, we have assessed ERV diversity through PCR surveys across species and within populations [2,3], and through interrogation of genomic data of key crocodilian species [6].…”
Section: Introductionmentioning
confidence: 99%